Physiologic adaptation problems in people with angina - Allyne Nóbrega Fortes; Viviane Martins da Silva; Marcos Venícios de Oliveira Lopes (Universidad de Alicante, 2012)
In this article the common physiologic adaptation problems presented by patients with unstable angina were identified, having as a base Callista Roy's Adaptation Model. A descriptive study was carried out in a specialized hospital for cardiac diseases. The sample for the study comprised a total of 20 patients. For characterization and discussion, we used the definitions presented by Roy for each physiologic adaptation problem identified. Regarding common physiologic adaptation problems, the following were identified: Activity intolerance, Constipation, Impairment of a primary sense: vision and audition, Nutrition in excess to body requirements, Sleep deprivation, Potential sleep pattern disturbance, Hyponatremia, Disuse syndrome, Restricted mobility, Anorexia, Memory deficit, Potential ineffective coping with allergic reaction, Stress, Oedema, Hypokalemia, Infection, Instability of Behavior and mood, and Delayed wound healing.